Changes during gonad maturation of female imbaw, Anodontia. - Lagrada, Jeselle A. (University of the Philippines Visayas, College of Arts and Sciences, Division of Biological Sciences, 2009)
Anodontia edentula, or imbaw, is an important shellfish resource in Panayand Guimaras. Its productive cycle was studied to gain insight on the process of gametogenesis in this species., The histological changes n the female gonad following spawning were described as well as changes in oocyte number and sizes after spawning. Gonad rematuration was monitored from week 0 (spent) to week 4 after spawning. Gametogenesis in female imbaw is contiuous. Following spawning increasing number of oocytes was observed in the follicles during the four week period. There was shift in predominant oocyte size of 0-5 um at week 1 to a majority of oocyte size in the range of 36-40 um at week 4. One follicle may contain varied oocyte sizes which may indicate that several batches of eggs are maturing at the same time. Spent ovaries showed residual oocytes after spawning suggesting partial spawning activity of imbaw, wherein not all mature oocytes are released at one time. The lack of mature vitellogenic oocytes in ovaries four weeks after spawning suggest it takes longer than a month for oocytes to mature and be spawned.